MANAJEMEN PENGELOLAAN GIZI DAN TINGKAT PENGETAHUAN ATLET DI SMA NEGERI OLAHRAGA PROVINSI RIAU - Sasmarianto, Sasmarianto (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
This study aims to determine the management of nutrition management and the level of knowledge of athletes in SMA Sports, Riau Province. This research method is descriptive qualitative. Data collection techniques used questionnaires, interviews, and documentation. Informants were selected by purposive sampling. Data were analyzed using triangulation techniques. The results showed that the management of athletes nutrition in Riau Province Sports High School had been working with the catering party. The level of knowledge of athletes about nutrition is in a good category. Athletes need a program that maintains and increases the athlete's knowledge of nutrition. Based on the results of the study, it can be concluded that 1) nutrition management in Riau Private State Senior High School provides food intake services for athletes based on applicable Standard Operating Procedures 2) athletes have a good level of knowledge about nutrition. Athletes also adopt a healthy lifestyle by consuming a balanced nutritious diet.